Chinese patent medicines combined with hormone replacement therapy for premature ovarian failure: A Bayesian network meta-analysis - Zhong, Han-Zhi; Li, Mao-Ya; Yin, Xiao-Lan; Bin, Cheng-Li; Zhou, Si-Yun; Wei, Shao-Bin (Frontiers in Medicine, 2022)
Objective The objective of this study was to compare the efficacy differences between Chinese patent medicines combined with hormone replacement therapy (HRT) in the treatment of premature ovarian failure (POF) by the Bayesian network meta-analysis (NMA) method. Methods Randomized controlled trials (RCTs) reporting Chinese patent medicine combined with HRT for POF included Medline (via PubMed), Embase, Cochrane Library, China National Knowledge Infrastructure Database (CNKI), Wanfang Database (Wanfang), VIP Database (VIP), and China Biology Medicine Database (CBM) from the inception of the databases to July 2022. Two researchers independently screened the articles, extracted data, and evaluated the quality. The literature that met the inclusion criteria was screened out, the quality and risk of bias of the included studies were assessed according to the Cochrane 5.1 manual and RevMan 5.4, and NMA was performed using Stata 15.0 and R software. Results Sixty-four RCTs involving 5,675 individuals containing 12 oral Chinese patent medicines combined with HRT were enrolled into the current NMA. The results showed that when compared with patients using only HRT, the total clinical response rate is greater in patients using HRT combined with one of these 12 oral Chinese patent medicines. Among them, Zuogui pills + HRT [odds ratio (OR) = 3.92; 95% credible interval (CrI) = 0.86, 23.84; SUCRA = 73.76%] is most likely to be the best intervention, and the suboptimal intervention is Guishen pills + HRT (OR = 3.22, 95% CrI = 1.16, 9.44, SUCRA = 70.60%). Conclusion Chinese patent medicines combined with HRT were more effective than HRT alone in the treatment of POF. Zuogui pills are good at decreasing follicle-stimulating hormone (FSH) and luteinizing hormone (LH) and more effective in the improvement of total clinical response rate; Xuefu Zhuyu capsule is also good at decreasing FSH. Ziheche capsule is an expert in improving estradiol level; Kuntai capsule shows the lowest incidence of adverse reactions. However, the quality of the literature included in this study is relatively low, so it may affect the results of the study. Therefore, higher quality and multi-center trial would be necessary for supporting these results. Systematic review registration [www.crd.york.ac.uk/prospero], identifier [CRD42022350587].